PENINGKATAN PENGETAHUAN MASYARAKAT MELALUI EDUKASI: PATUHI, OBATI DAN KENDALIKAN DIABETES - Hariadi, Puspawan; Oktresia, Erma Ewisa; Sovia, Fitriwati; Gemantari, Baiq Maylinda (LPPM Universitas Bina Bangsa, 2025)
Diabetes Mellitus (DM) can lead to various complications, both macrovascular and microvascular. Diabetes education interventions play a crucial role in DM management, as they help improve patients' knowledge and adherence to diabetes management strategies. This study involved three sessions: a pre-test, an educational session, and a post-test. Among 53 respondents, the proportion of participants with a high level of knowledge increased from 30 (56.6%) to 43 (81.1%). Meanwhile, those with a low level of knowledge decreased from 10 (18.9%) to 1 (1.9%). This increase in knowledge levels demonstrates the effectiveness of the education provided. The average pre-test knowledge score was 69.06, compared to a post-test score of 86.23, demonstrating a significant improvement. Wilcoxon test analysis showed a significance value of <0.05. Thus, the